2021
DOI: 10.18438/eblip29871
|View full text |Cite
|
Sign up to set email alerts
|

Moral Distress Among Consumer Health Information Professionals: An Exploratory Study

Abstract: Objectives – In recent years, moral distress has become a topic of interest among health professionals. Moral distress is most commonly described in the nursing literature, and refers to a situation wherein an individual knows the correct action to take, but is constrained from doing so. While moral distress differs from the classic ethical dilemma, in recent years practitioners and theorists have advocated for a broadening of the definition of moral distress. To date, no study has examined another group of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Similarly, O'Hanlon et al. (2021, p. 57, 62) indicated that higher moral distress among Black and Latinx Consumer Health Information Professionals in a USA study was linked to race relations. Black and Latinx respondents were more likely to feel frustrated with role confusion, report feeling required to provide positive responses to patron inquiries, provide prognosis information and more likely to fear for their safety at work.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Similarly, O'Hanlon et al. (2021, p. 57, 62) indicated that higher moral distress among Black and Latinx Consumer Health Information Professionals in a USA study was linked to race relations. Black and Latinx respondents were more likely to feel frustrated with role confusion, report feeling required to provide positive responses to patron inquiries, provide prognosis information and more likely to fear for their safety at work.…”
Section: Resultsmentioning
confidence: 92%
“…Two studies highlighted the moral distress experiences of gender‐diverse health professionals or trainees. One study found that non‐binary participants disproportionately responded “strongly agree” with a survey question on feeling pressured to provide prognosis information (O'Hanlon et al., 2021). The other found that sexual orientation was not a predictor of vitality, an institutional cultural dimension observed to be strongly predicted by moral distress (Pololi et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation